Ultrastructural study of the ventral lobe of the prostate of mice with streptozotocin induced diabetes (C57BL/6J) - Cagnon, V. H.A.; Camargo, A. M.; Rosa, R. M.; Fabiani, R.; Padovani, C. R. [UNESP]; Martinez, F. E. [UNESP] (Elsevier, 2000)
Morphological and functional changes caused by diabetes in the accessory sex organs andespecially the prostate have been reported by several investigators. The aim of the present study was to examine the possible deleterious effects of experimentally induced diabetes on the secretory epithelium of the ventral prostate of mice. Sixteen adult male C57BL/6J mice were divided into two groups. The diabetic group received streptozotocin injection of 75 mg/kg while the control group received only 0.1 ml citrate buffer i.p. After 30 days the diabetic state was ascertained the animals were sacrificed and the ventral lobe of the prostate was collected for histological and ultrastructural examination. The results showed reduction in glandular epithelium cell height increased numbers of cytoplasmic vacuoles and thickening of the extracellular matrix.In conclusion experimental diabetes has harmfuleffects on the secretory epithelial cells of theventral lobe of the prostate of mice. (C) 2000 Harcourt Publishers Ltd.
Keywords: Diabetes; Prostate; Ultrastructural